Magnetic Resonance Imaging and Histopathologic Findings From a Standard Poodle With Neonatal Encephalopathy With Seizures - Yu, Yoshihiko; Hasegawa, Daisuke; Chambers, James K.; Kojima, Kazuhiro; Asada, Rikako; Johnson, Gary S.; Uchida, Kazuyuki (Frontiers in Veterinary Science, 2020)
Neonatal encephalopathy with seizures (NEwS) is an epileptic encephalopathy with an autosomal recessive inheritance pattern found in Standard Poodle puppies. The causal genetic variant for NEwS has been identified as a homozygous missense mutation in ATF2 (c.152T>G, p.Met51Arg), and a pathological cerebellar change has been reported. Magnetic resonance imaging showed reduced whole-brain size, dilated ventricles, developmental abnormalities of the white matter of the cerebrum, white matter signal abnormalities in the occipital lobe, and abnormal morphology of the cerebellum. Histopathology included previously unrecognized irregular neuronal migration in the subventricular zone around the lateral ventricles in the frontal lobe and white matter rarefaction especially at the level of the occipital lobe in the cerebrum in addition to the cerebellar cortical dysplasia that has been previously described. The findings of this case may highlight the critical role of ATF2 in neurodevelopmental processes in the canine brain.